Posterior Glenoid Osteotomy With Capsulolabral Repair Improves Resistance Forces in a Critical Glenoid Bone Loss Model. Issue 3 (15th March 2022) - Marcaccio, Stephen E.; O'Donnel, Ryan M.; Schilkowsky, Rachel; Owens, Meng Brett D.; Bokshan, Steven L.
Background: There is no widespread consensus on the surgical treatment of posterior shoulder instability with critical posterior glenoid bone loss. Hypothesis: That opening posterior glenoid wedge osteotomy with soft tissue repair would improve the resistance forces of instability when compared with soft tissue repair alone in the setting of 20% critical bone lose. Study Design: Controlled laboratory study. Methods: Native glenoid retroversion was measured on 9 shoulders using computed tomography (CT) scans. The humerus was potted in 90° of forward flexion and 30° of internal rotation relative to the scapula, and a posterior dislocation was performed to create a posterior capsulolabral injury model. The specimens were each taken through a fixed sequence of testing: (1) posteroinferior capsulolabral tear, (2) no glenoid bone loss with posteroinferior capsulolabral repair, (3) 20% posterior glenoid bone loss with posteroinferior capsulolabral repair, and (4) 20% glenoid bone loss with posterior glenoid opening wedge osteotomy and posteroinferior capsulolabral repair. Bone loss was created using a sagittal saw. The resultant peak forces with 1 cm of posterior translation were measured. A 1-way repeated-measures analysis of variance was used to compare mean force values. Results: After the initial dislocation event, all shoulders had a resultant posterior capsulolabral injury. The resulting labral injury was extended from 6- to 9-o'clock in all specimens to homogenize the extent of injury. Repairing the capsulolabral complex in the 20% posterior glenoid bone loss group did not result in a statistically significant increase in resistance force compared with the labral deficient group (34.1 vs 22.2 N; P = .068). When 20% posterior bone loss was created, the posterior glenoid osteotomy with capsulolabral repair was significantly stronger (43.8 N) than the posterior repair alone both with (34.1 N) and without (31.8 N) bone loss ( P = .008 and .045, respectively). Conclusion: In the setting of critical posterior glenoid bone loss, an opening wedge posterior glenoid osteotomy with capsulolabral repair improved resistance to posterior humeral translation significantly compared with capsulolabral repair alone. Clinical Relevance: The results of this biomechanical cadaveric study may aid in surgical planning for this complex patient population.